Implementasi Kebijakan Merdeka Belajar Kampus Merdeka Di Universitas Muhammadiyah Jakarta - Farah Shafira Firmanto; Evi Satispi (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
This article discusses the implementation of the Independent Campus Learning Policy at Muhammadiyah University Jakarta. The aim of this research is to find out and analyze the implementation of the independent campus learning policy at the Muhammadiyah University in Jakarta. This research theory uses policy implementation theory in the George Edwards III model. By using descriptive methods and qualitative approaches. Data collection uses interview, observation and documentation methods. The research results from 4 (four) indicators show that communication needs to be carried out more massively because there are several lecturers who do not understand the conversion and know the mechanisms in the Independent Learning Campus policy. Resources are sufficient, but supervision needs to be increased because there is still a lack of supervision. Disposition, having responsibility as evidenced by commitment to implementing the Independent Campus Learning Policy. Bureaucratic structure, policies are carried out in accordance with SOP. The technical data analysis carried out is data collection, data reduction, data presentation and drawing conclusions. The results of the research show that the implementation of the Merdeka Belajar Campus Merdeka policy is good, but it is hoped that it will be further improved regarding technical matters regarding Merdeka Belajar Campus Merdeka as well as providing an information system (IT) to make it easier to implement Merdeka Belajar Campus Merdeka.